CCBuilder 2.0: Powerful and accessible coiled‐coil modeling. (15th September 2017) - Wood, Christopher W.; Woolfson, Derek N.
Abstract: The increased availability of user‐friendly and accessible computational tools for biomolecular modeling would expand the reach and application of biomolecular engineering and design. For protein modeling, one key challenge is to reduce the complexities of 3D protein folds to sets of parametric equations that nonetheless capture the salient features of these structures accurately. At present, this is possible for a subset of proteins, namely, repeat proteins. The α‐helical coiled coil provides one such example, which represents ≈ 3–5% of all known protein‐encoding regions of DNA. Coiled coils are bundles of α helices that can be described by a small set of structural parameters. Here we describe how this parametric description can be implemented in an easy‐to‐use web application, called CCBuilder 2.0, for modeling and optimizing both α‐helical coiled coils and polyproline‐based collagen triple helices. This has many applications from providing models to aid molecular replacement for X‐ray crystallography, in silico model building and engineering of natural and designed protein assemblies, and through to the creation of completely de novo "dark matter" protein structures. CCBuilder 2.0 is available as a web‐based application, the code for which is open‐source and can be downloaded freely.http://coiledcoils.chm.bris.ac.uk/ccbuilder2 . Lay Summary: We have created CCBuilder 2.0, an easy to use web‐based application that can model structures for a whole class of proteins, the α‐helical coiled coil, which is estimated to account for 3–5% of all proteins in nature. CCBuilder 2.0 will be of use to a large number of protein scientists engaged in fundamental studies, such as protein structure determination, through to more‐applied research including designing and engineering novel proteins that have potential applications in biotechnology.